Effect of ZrO2 on the sintering behavior, strength and high-frequency dielectric properties of electrical ceramic porcelain insulator. (24th January 2018) - Mehta, Niraj Singh; Sahu, Praveen Kumar; Ershad, Md; Saxena, Vipul; Pyare, Ram; Majhi, Manas Ranjan
Abstract: In the present study, the effect of ZrO2 on the sintering, strength and dielectric behavior of electrical ceramic porcelain insulator with substituting alumina content by zirconia (in weight percentage from 0% to 30%) is investigated. The different composition of samples containing different zirconia (ZrO2 ) contents of 0, 10, 20, and 30 wt% are prepared using the uniaxial pressure technique applying 160 MPa pressure. Further, the prepared samples are also analyzed for sintering temperatures (1350 °C), and effects are observed on mechanical and electric properties of porcelain insulator. Different characterizations such as Dilatometer, x-ray diffraction, scanning electron microscopy and differential thermal analysis/thermo gravimetric analysis were used to evaluate the thermal, phase detection, micro structural and weight loss changes by increasing concentration of ZrO2 on base porcelain composition. At 1350 °C, for the composition having 20 wt% ZrO2 with 10 wt% alumina, the maximum density was observed 2.81 g cm −3 with a porosity of 2.23%. The highest tensile strength of 41 ± 3 MPa is observed for the same sample composition. The minimum value of thermal expansion coefficient is found to be in the range of 10 −6 for the sample with 30 wt% ZrO2 content sintered at 1350 °C compared to other prepared samples. Similarly, the highest dielectric value (5.1–4.4) having dielectric loss (0.08–0.12) is achieved for the sample with 30 wt% ZrO2 content sintered at 1350 °C in the frequency range of 4–20 GHz at room temperature. According to the mechanical properties, the composition having 20 wt% ZrO2 on base ceramic porcelain composition has enormous potential to serve as a high strength refractory material. For dielectric properties, the composition having 30 wt% ZrO2 is more suitable for the electrical application.